2022
DOI: 10.20944/preprints202206.0336.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cell division controls final fruit size in three apple (Malus x domestica) cultivars

Abstract: Apple (Malus x domestica) fruit size is dependent on cell division and cell expansion, processes which are subsequently regulated by plant hormones such as auxins, gibberellins, and cytokinins. In this study, we investigated the role of cell division and cell expansion in apple growth and identified which of the two was more deterministic to final fruit size. Three cultivars of different sizes were selected, namely, ‘Twenty Ounce’ (large-sized), ‘Royal Gala’ (medium-sized), and ‘Crabapple’ (small-sized). Gene … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…It has been reported that both cell division and expansion rates determine the number and size of mesocarp cells and thus the size of ripe fruit in apple. However, cell division was once proposed key to the differences in fruit size among cultivars, because the cell areas of each cultivar, 'Twenty Ounce' (large-sized), 'Royal Gala' (medium-sized), and crab apple (small-sized), were similar at pollination or at ripening (Karim, 2015;Karim et al, 2022). By using an interspeci c hybrid population, we con rmed that no considerable differences were found in mesocarp cell size between large-fruit and small-fruit groups but mesocarp cell number of large-fruit group was signi cantly higher than that of small-fruit group (Figure 2a, 2b).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that both cell division and expansion rates determine the number and size of mesocarp cells and thus the size of ripe fruit in apple. However, cell division was once proposed key to the differences in fruit size among cultivars, because the cell areas of each cultivar, 'Twenty Ounce' (large-sized), 'Royal Gala' (medium-sized), and crab apple (small-sized), were similar at pollination or at ripening (Karim, 2015;Karim et al, 2022). By using an interspeci c hybrid population, we con rmed that no considerable differences were found in mesocarp cell size between large-fruit and small-fruit groups but mesocarp cell number of large-fruit group was signi cantly higher than that of small-fruit group (Figure 2a, 2b).…”
Section: Discussionmentioning
confidence: 99%
“…For fruit set to take place, pollination and fertilisation must be accomplished or the flowers will be abscised [13,15,16]. Pollination is the crucial starting point in fruit development as it is required for fertilisation.…”
Section: Fruit Development 21 Stages Of Fruit Developmentmentioning
confidence: 99%
“…Pollination is the crucial starting point in fruit development as it is required for fertilisation. During fruit set, rapid cell division occurs and then stops when the fruit reaches its mature size [16][17][18]. Levels of plant hormones, such as auxins, CKs (CKs), and gibberellic acids (GAs), increase to promote fruit set [13,16].…”
Section: Fruit Development 21 Stages Of Fruit Developmentmentioning
confidence: 99%
See 1 more Smart Citation